OP0269 HPR PATTERNS OF FATIGUE AND PREDICTORS OF SIGNIFICANT IMPROVEMENT IN THE 1ST YEAR OF RA: RESULTS FROM THE CANADIAN EARLY ARTHRITIS COHORT (CATCH). (June 2019) - Bartlett, Susan J.; Schieir, Orit; Valois, Marie-France; Hitchon, Carol; Bessette, Louis; Hazlewood, Glen; Thorne, Carter; Pope, Janet; Boire, Gilles; Tin, Diane; Keystone, Edward; Bykerk, Vivian; et al.
Abstract : Background: Fatigue is common in early RA(ERA) and though some patients experience improvement in fatigue when disease is well controlled, others experience persistent fatigue associated with work disability, poor QOL, and depression. Objectives: To compare patterns and predictors of improved vs. persistent fatigue in the first year of ERA. Methods: Data were from ERA patients (symptoms <1 year) enrolled in the Canadian Early Arthritis Cohort (CATCH) from 01-2007 to 03-2017. All met ACR1987 or 2010 ACR/EULAR criteria, had active disease, were on DMARDS, and complete fatigue (0-10) data over ≥ 12 months. Patients were classified at baseline with low (<4) or high (≥4) fatigue; high fatigue patients were categorized at 12-months as improved (↓ ≥2) or persistent (↓ <2). Multivariable logistic regression was used to identify predictors of improved vs. persistent fatigue at 12 months in those with high baseline fatigue. Results: The 1002 pts were mostly white (81%), female (71%), with a mean (SD) age of 54 (15); 32% were obese. 70% had high fatigue at baseline; these patients were more obese, had OA/backpain, poor sleep, depression, major stress, and higher disease activity (Table 1). Among those with initial high fatigue, 30% had persistent fatigue at 12 months and was associated with obesity, comorbidities, FM, longer symptom duration, and slightly lower baseline fatigue. Predictors of improved fatigue in multivariable models were BMI<30 (OR 0.6; 95% CI 0.4, 0.9), MTX≥20 mg (OR 1.7; 95% CI 1.0, 2.7) and higher pain (OR 1.1; 95% CI 1.0, 1.2) after controlling for other variables. Conclusion: Fatigue is common in ERA and associated with active disease, worse pain and disability, obesity, depression, major stressors, poor sleep and OA/backpain. In high fatigue pts, those who are not obese, have higher pain, and take ≥20 mg MTX are more likely to improve over the first year. Optimizing weight, sleep, physical and emotional health and MTX use may improve persistent fatigue beyond control of RA inflammation. Disclosure of Interests: Susan J. Bartlett Consultant for: Pfizer, UCB, Lilly, Novartis, Merck, Jansen, Abbvie, Orit Schieir: None declared, Marie-France Valois: None declared, CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Louis Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Glen Hazlewood: None declared, Carter Thorne Grant/research support from: Investigator-initiated studies: Amgen, Pfizer. RCTs: Abbvie, Celgene, CaREBiodam, Novartis, Pfizer, Consultant for: Advisory board: Abbvie, Amgen, Celgene, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi. Consultant: Abbvie, Centocor, Janssen, Lilly, Medexus/Medac, Pfizer, Speakers bureau: Medexus/Medac, Janet Pope Consultant for: Eli Lilly and Company, Gilles Boire Grant/research support from: Investigator-initiated studies: Amgen, Abbvie, BMS, Eli Lilly, Merck, Novartis, Pfizer, Consultant for: Advisory boards: Amgen, BMS, Celgene, Eli Lilly, Pfizer, Speakers bureau: Merck, BMS, Pfizer, Diane Tin: None declared, Edward Keystone Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, F. Hoffmann-La Roche Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, Consultant for: AbbVie, Amgen, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Celltrion, Crescendo Bioscience, F. Hoffmann-La Roche Inc, Genentech Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, Sandoz, UCB., Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Merck, Pfizer Pharmaceuticals, Sanofi Genzyme, UCB, Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron